Use of medicinal plants for therapeutic purposes by High School students (Research, Society and Development, 2021)
Medicinal plants are used as a food and therapeutic resource by civilizations throughout human history. However, knowledge at the biological level is rarely discussed in the classroom. Thus, the study aimed to survey the knowledge of high school students about the use of medicinal plants for therapeutic purposes in a public school in the state of Piauí. Thus, data were collected by electronic form and applied to 33 high school students from public schools in the state of Piauí. Then, the data were subjected to descriptive statistical analysis of frequency and analytical categories for qualitative data. The students cited 17 specimens of plants, where tea and leaves were the main forms of use and preparation, respectively. The plants were used, mainly in the treatment of respiratory and gastrointestinal problems, and the most cited specimens were mint and lemon balm. It was also observed that the students had fragmented knowledge about medicinal plants' therapeutic purposes and the possible damages caused to the genetic material. As plants are a natural resource, students believed that they did not cause damage to the organism. Thus, it appears that traditional knowledge about medicinal plants is present in the lives of students, despite the little associated scientific knowledge.